Cover. Issue 8 (18th August 2020) - Yang, Mingxin; Weng, Qinjie; Pan, Xiaoxia; Hussain, Hafiz Muhammad Jafar; Yu, Shuwen; Xu, Jing; Yu, Xialian; Liu, Yunzi; Jin, Yuanmeng; Zhang, Chunli; Li, Xiao; Ren, Hong; et al.
Abstract : The cover image is based on the Original Article Clinical and Genetic Analysis of LPG patients caused by APOE mutations by Jingyuan Xie et al., https://doi.org/10.1002/mgg3.1281